Resonant-boost LC converter base charge balancing system for electric vehicle - Rahman, Mizanur; Rashid, Muhammad Mahbubur; Rahman, Mohammed Ataur; Khan, Sheroz (Asian Research Publishing Network (ARPN), 2016)
Cell voltage equalization is essential in a battery pack to guarantee high performance, safety and extend the lifetime by eliminating the charge unbalancing problem. Many conventional charge balancing systems have been designed and developed to solve this problem. Besides this, there are some problems still exist: switching power loss and longer charge balancing time that lead to a less efficient charge balancing system. In this paper, resonant-boost LC converter base charge balancing system has been proposed. The switching power loss in the switching components is reduced by achieving zero current switching and the speed of balancing is substantially accelerated using a resonant boost converter. In the simulation, the result of charge balancing with current and voltage characteristics of a series connected cells has been shown. The result shows that the balancing process is substantially improved.